2016
DOI: 10.15207/jkcs.2016.7.4.107
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Study on the Influence of Job Stress of Shift Work Nurses on Nursing Performance

Abstract: This study aimed to seek the way of effectively managing job stress of shift work nurses, to improve nursing performance, the influence of job stress of shift work nurses on nursing performance through convergence research. A total of 244 questionnaires obtained by a survey targeting nurses, who were doing shift work in a university hospital located in B city, in the period from March 2 to 15, 2015 were analyzed using the SPSS 21.0 program. As a result, the mean score of job stress was 3.57 points, and the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…When considering that the psychological and physical stress scores of 20 or higher fall under the warning level [ 5 , 6 , 9 ], which is risky and requires considerable attention or evaluation from a specialist, the stress level of the subjects was very high. In the study of Choi [ 29 ], the results of the comparison between fixed shift and rotating shift nurses in regard to physical, social, sleep, and mental stress showed that the stress level of the rotating shift nurses was higher than that of the fixed shift nurses. In the present study, the psychological and physical stress scores were statistically significantly reduced as a result of performing acupressure on shiftwork nurses after their daytime shift, thereby indicating that acupressure had an effect on stress reduction.…”
Section: Discussionmentioning
confidence: 99%
“…When considering that the psychological and physical stress scores of 20 or higher fall under the warning level [ 5 , 6 , 9 ], which is risky and requires considerable attention or evaluation from a specialist, the stress level of the subjects was very high. In the study of Choi [ 29 ], the results of the comparison between fixed shift and rotating shift nurses in regard to physical, social, sleep, and mental stress showed that the stress level of the rotating shift nurses was higher than that of the fixed shift nurses. In the present study, the psychological and physical stress scores were statistically significantly reduced as a result of performing acupressure on shiftwork nurses after their daytime shift, thereby indicating that acupressure had an effect on stress reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Also, nurses who are more educated tend to make better patient care decisions by drawing on their knowledge from advanced study (Khan, Jackson, Stayt, & Walthall, 2018). On the other hand, several studies have indicated that increases in night shifts caused physical problems for nurses and thus negatively influenced their nursing performance (Choi, Heo, & Moon, 2016; Johnson, Brown, & Weaver, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Work-related stress is inevitable for nurses. An appropriate amount of tension can improve nursing care outcomes and motivate personal growth as well as enhance task productivity (Choi et al, 2016). In stressful situations, nurses may choose to transfer to a different department or quit; however, they can also demonstrate their capabilities as nursing professionals by overcoming and adjusting to difficult situations (Mealer et al, 2012).…”
Section: Ta B L E 4 Factors Affecting Triage Competence (N = 156)mentioning
confidence: 99%